Time to try again - Parent, Nancy; Ibrahim, Dalia Mohamed; Maruyama, Jerrod (Giza, Egypt nahdet misr publishing house, 2023)
Gilbert learns not to be sad when he fails in doing something. He shouldn't give up and keep trying until he succeeds
English stories
for child from 7 years to 10 years
Keywords: English stories